Hemorrhagic Stroke in a Young Adult with Undiagnosed Asymptomatic Dandy–Walker Malformation - Haleem Abdul; Joseph Burns; Andrea Estevez; Carlos Nasr El-Nimer; Brinsley Ekinde; Sherard Lacaille (Case Reports in Neurological Medicine)
The Dandy–Walker Malformation was first described in 1914 by Dandy and Blackfan and is characterized by hypoplasia of the vermis, pseudocystic fourth ventricle, upward displacement of the tentorium, torcular and lateral sinuses, and anteroposterior enlargement of the posterior fossa. This syndrome commonly manifests as hydrocephalus in children, though rare adult cases have been reported. The literature reveals adult symptomatology including brainstem infarction, psychosis, and neuromuscular disease. Stroke is an exceptionally rare presentation of this malformation, with only one ischemic event reported in the literature. This case offers a rare opportunity for diagnosis in an adult presenting with a hemorrhagic stroke of the basal ganglia in an otherwise asymptomatic young adult male. To the best of our knowledge, this is the first reported case of a hemorrhagic stroke in an adult patient with Dandy–Walker Malformation.